Majority-Logic, its applications, and atomic-scale embodiments. (May 2020) - Parhami, Behrooz; Abedi, Dariush; Jaberipur, Ghassem
Abstract: Today's computing is increasingly data-intensive, heralding the age of big data. With greater data volumes, come the needs for faster processing, greater storage capacity, and expanded communication bandwidth, all of which imply the expenditure of more energy. Thus, energy efficiency, already a major design consideration, will assume broader significance in the coming years. As important as storage and communications are, our focus in this paper is on better technology to reduce the computation (logic manipulation) power. We review majority logic, a special case of threshold logic, show how a number of common arithmetic/logic operations can be performed using the majority-gate primitive, and review an impressive array of atomic-scale logic technologies that are particularly efficient in realizing the majority or minority function. We conclude that a combination of orders of magnitude energy reduction by virtue of the technology used and implementation strategies that lead to comparable complexity in terms of majority gates when contrasted with currently used circuit primitives (AND, OR, XOR, NOT, mux) leads to energy-efficient realization of arithmetic/logic functions suitable for use in the age of big data.